Repeatabılıty Of Subjectıve Determınatıon Of Natural Head Posıtıon, In Subjects Wıth Dıfferent Profıle Confıguratıons - M. Murat Özbek; Ayşegül Köklü; Banu Erdoğan (Galenos Yayinevi, 1993)
This study was carried out on lateral cephalograms of 27 subjects and aimed at determining the effect of profile configuration in subjective determination of natural head position. Three subgroups were formed comprising orthognathic, prognathic and retrognathic subjects. "Intraclass correlation coefficients" were used to assess the intra- and inter-observer repeatability of double determinations. Despite the statistically significant correlation coefficients in the main study sample, low correlations were observed in the subgroups. The repeatability was especially low (statistically insignificant) in the orthognathic subgroup.